2016
DOI: 10.54652/rsf.2016.v46.i1.80
|View full text |Cite
|
Sign up to set email alerts
|

Damage on Standing Trees During Wood Skidding (Winching Phase) by Cable Skidder Timberjack 225 A

Abstract: UDK: 630*37:630*4     Hauling of heavy and voluminous load (wood) partially through forest wastelands and partially on built roads makes this the most expensive phase, which is also technically the most challenging and most damaging for the forest eco-system. Although it is clear that the realisation of this phase in forest harvesting cannot be completed without certain forest damage, in expert and scientific circles there is general consent that by careful planning and execution in forestry, this damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 3 publications
(3 reference statements)
0
9
1
Order By: Relevance
“…Behjou [36] claimed that the probability of individual tree damage decreased as the skid road cross slope decreased and the distance to the skid road edge increased. Considerable research has confirmed the thesis that the number of damaged residual trees is reduced with increasing distance from the center of the skid roads [2,34,[37][38][39].…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Behjou [36] claimed that the probability of individual tree damage decreased as the skid road cross slope decreased and the distance to the skid road edge increased. Considerable research has confirmed the thesis that the number of damaged residual trees is reduced with increasing distance from the center of the skid roads [2,34,[37][38][39].…”
Section: Introductionmentioning
confidence: 90%
“…The damage was classified as squeezed bark, removed bark, and damaged wood by damage severity [7,28,36,39], as shown in Figure 4. An ox is a castrated bull trained and used for draught work.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations